2019
DOI: 10.1176/appi.ajp.2018.18030280
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Olanzapine-Induced Weight Gain With Samidorphan, an Opioid Antagonist: A Randomized Double-Blind Phase 2 Study in Patients With Schizophrenia

Abstract: Preclinical evidence and data from a proof-ofconcept study in healthy volunteers suggest that samidorphan, an opioid antagonist, mitigates weight gain associated with olanzapine. This study prospectively compared combination therapy of olanzapine plus either samidorphan or placebo for the treatment of schizophrenia.Methods: This was an international, multicenter, randomized phase 2 study of olanzapine plus samidorphan in patients with schizophrenia. The study had a 1-week open-label olanzapine lead-in period f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
103
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 39 publications
4
103
0
Order By: Relevance
“…In a phase 1 study in healthy adults, less weight gain was observed in subjects who received a combination of OLZ (10 mg) and SAM (5 mg) compared with subjects who received OLZ (10 mg) alone . In a subsequent phase 2 study, coadministration of OLZ with SAM (5, 10, and 20 mg) mitigated OLZ‐induced weight gain in adults with schizophrenia . In addition to being developed in combination with OLZ for the treatment of schizophrenia, SAM (at a 2‐mg dose) is also under evaluation in a fixed‐dose combination with buprenorphine for a proposed indication as adjunctive treatment of major depressive disorder …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a phase 1 study in healthy adults, less weight gain was observed in subjects who received a combination of OLZ (10 mg) and SAM (5 mg) compared with subjects who received OLZ (10 mg) alone . In a subsequent phase 2 study, coadministration of OLZ with SAM (5, 10, and 20 mg) mitigated OLZ‐induced weight gain in adults with schizophrenia . In addition to being developed in combination with OLZ for the treatment of schizophrenia, SAM (at a 2‐mg dose) is also under evaluation in a fixed‐dose combination with buprenorphine for a proposed indication as adjunctive treatment of major depressive disorder …”
mentioning
confidence: 99%
“…6 In a subsequent phase 2 study, coadministration of OLZ with SAM (5, 10, and 20 mg) mitigated OLZ-induced weight gain in adults with schizophrenia. 7 In addition to being developed in combination with OLZ for the treatment of schizophrenia, SAM (at a 2-mg dose) is also under evaluation in a fixed-dose combination with buprenorphine for a proposed indication as adjunctive treatment of major depressive disorder. 8 OLZ/SAM is formulated as an immediate-release bilayer tablet for once-daily oral administration, with one layer containing OLZ and the other layer containing SAM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase 1 study in healthy volunteers, weight gain was significantly lower in those treated with OLZ/SAM than those treated with olanzapine monotherapy. 20 In a subsequent phase 2 study 21 in patients with schizophrenia who were clinically stable (defined as a Positive and Negative Syndrome Scale [PANSS] score ≤ 80 and a Clinical Global Impressions-Severity of Illness Scale [CGI-S] score ≤ 3 at screening), the antipsychotic efficacy of OLZ/SAM was similar to that of olanzapine; the presence of samidorphan mitigated olanzapine-associated weight gain, although a difference in weight gain was not observed until after 4 weeks of treatment.…”
Section: E2mentioning
confidence: 99%
“…10,11 In vivo, it has been established that samidorphan functions as an opioid receptor antagonist. 12 In studies enrolling healthy adult subjects 13 and adult patients with schizophrenia, 14 the presence of samidorphan limited olanzapine-induced weight gain in those receiving OLZ/SAM vs. olanzapine alone.…”
mentioning
confidence: 99%